The place to be : Crac Alsace catalogue 2003-2004. - Brandt, Charlotte; Doove, Edith; Jian, Qin; Teerlinck, Hilde; Torres, David G.; Crac Alsace, Altkrich (Altkirch : CRAC (Centre Rhenan d'Art Contemporain) Alsace Altkirch, 2004)
't Jolle, Sven ; Ai Weiwei ; Anson, Marti ; Asaoka, Akané ; Bai Yiluo ; Baojun Rui ; Baudy, Regis ; Beecroft, Vanessa ; Blanckart, Olivier ; Bourdarel, Katia ; Bourgeois, Louise ; Bulloch, Angela ; Cadieux, Geneviève ; Cattelan, Maurizio ; Celikdag, Timur ; Chang, Patty ; Chivas, Clem ; Chotard, Gaëlle ; Collishaw, Mat ; Courreges, François-Xavier ; Daquet, Marianne ; Declercq, Alain ; Delvigne, Denys ; Demongeot, Romain ; Desmeules, Cécile ; Dispositive Sound System ; Dong Xing ; Düring, Irene ; Duyvendak, Yan ; Eder, Martin ; Fahlström, Unn ; Fayard, Ivan ; Gilbert & George ; Golia, Piero ; Hai Bo ; Hausswolff, Annika von ; Heijne, Mathilde ter ; Holzer, Jenny ; Janssens, Ann Veronica ; Just, Jesper ; Kimsooja ; Korine, Harmony ; Krystufek, Elke ; Lange, Andrea ; Laurette, Matthieu ; Leutenegger, Zilla ; Lin Lin & Jia Wen Hou ; Lin Xi & Fish ; Lucas, Sarah ; Mafille, Emmanuelle ; Marchetti, Corinne ; Maric, Marianne ; Mattelli, Tony ; Menini, Fiorenza ; Meurant, Alexandra ; Miao, Xiaochun ; Michel, Chantal ; Millagou, Olivier ; Moulène, Jean-Luc ; Myskja, Tone ; Nicolai, Olaf ; Niemi-Junkola, Fanni ; Orta, Lucy ; Palacin, Mabel ; Pane, Gina ; Planes, Bertrand ; Poirot, Sonia ; Premier Mais ; Prost, Christophe ; Qi Zhilong ; Quieros, Francisco ; Raeven, L.A. ; Raila, Arturas ; Rappenecker, Gert ; Reinhard, Aurora ; Rist, Pipilotti ; Rönicke, Pia ; Shen Ye ; Ström, Annika ; Tang Nan Nan ; Tanguy, Arnaud ; Tuerlinckx, Joëlle ; Vogt, Alexandra ; Wang Jin ; Wang Yi Ji ; Wekua, Andro ; Wurm, Erwin ; Xie Nanxing ; Y-F Yuen ; Yoshiko, Seino ; Zanni, Margot ; Zeng Huan Guang ; Zhou Xiaohu ; Zhuang Hui
Engels
Frans
Catalogus 2003-2004 van tentoonstellingen in Crac Alsace, ALtkrich
boek